The principle of effective demand in the short and the long run: Marx, Kalecki, Keynes, and beyond - Eckhard Hein (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
The principle of effective demand, and the claim of its validity for a monetary production economy in the short and in the long run, is the core of heterodox macroeconomics, as currently found in all the different strands of post-Keynesian economics (Fundamentalists, Kaleckians, Sraffians, Kaldorians, Institutionalists) and also in some strands of neo-Marxian economics, particularly in the monopoly capitalism and underconsumptionist school. In this contribution, we will therefore outline the foundations of the principle of effective demand and its relationship with the respective notion of a capitalist or a monetary production economy in the works of Marx, Kalecki and Keynes. Then we will deal with heterodox short-run macroeconomics and provide a simple short-run model, which is built on the principle of effective demand, as well as on distribution conflict between different social groups (or classes): rentiers, managers and workers. Finally, we will move to the long run and we will review the integration of the principle of effective demand into some variants of heterodox/post-Keynesian approaches towards distribution and growth, the Kaldor-Robinson, the Kalecki-Steindl and the Sraffian Supermultiplier model.
Keywords: E20; E21; E22; E24; E25; 330; Effective demand; employment; distribution; growth; Marx; Kalecki; Keynes